Legal protection for financial abuse among elderly in Malaysia - Ramli, Siti Raudhah; Fauzi, Husna; Roslan, Amirah Khadijah (Secholian Publication, 2023)
ABSTRACT Elder financial abuse was claimed to be under-reported. In the literatures, there are many discussions on the elder financial abuse but there was scarcity in the discussion of elder financial abuse in legal context. This paper aims to identify the legal protection related to elder financial abuse in Malaysia. The method used in this paper is the doctrinal method and qualitative study approach based on content analysis, where the Domestic Violence Act 1994 (DVA), the Malaysian Penal Code (PC), the Contracts Act 1950 (CA) and case laws will be analysed. The results show the legal protection on the issue of elder financial abuse and the remedies available for the elderly in Malaysia. Elder financial abuse can happen in domestic violence, contract and criminal cases. The perpetrator involved could be strangers or someone with trust. The remedies available are also differ depending on the cases.